Membangun Kesehatan Mental Sebagai Upaya Pencegahan Bullying Pada Anak-anak Rumah Belajar Kojartis Melalui Permainan “True Friends” Projek Kepemimpinan Mahasiswa PPG Prajabatan Universitas PGRI Palembang - Kirana, ST Fianda; Hanindiya, Nur Azmi; Andriyani, Irma; S, Salsabila; R, Rohani; M, Murjainah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The form of game that will be designed to build mental health in an effort to bully Kojartis children is the "True Friends" game. True Friends is designed to encourage children to learn values such as friendship, empathy, and cooperation through fun, interactive activities. In this way, children learn to better manage their emotions and social interactions, reducing their risk of becoming perpetrators or victims of Bullying. The approach used in this research is a qualitative approach. A qualitative approach is research whose object is natural in nature where the researcher is the key instrument, sampling of data sources is carried out purposively and snowballing, data analysis is inductive and the results of qualitative research emphasize meaning rather than generalization. This "True Friends" activity was carried out as an effort to strengthen the mental health of the children of the Kojartis Palembang Learning House and prevent Bullying behavior through the educational game approach "True Friends." Based on the information we got from the Kojartis Learning House administrators, there are 15 children with an age range of 12-15 years at the elementary-middle school education level. So we divided the Kojartis learning house children into two groups. This aims to ensure that all children have the same opportunity to become winners in the "True Friends" activity. This activity was carried out on August 24 2024 and was attended by the Kojartis Learning House administrators, Kojartis Learning House children, and all members of the Leadership Project group.